2008
DOI: 10.1103/physrevc.77.054319
|View full text |Cite
|
Sign up to set email alerts
|

Two-step γ cascades following thermal neutron capture inMo95

Abstract: A strong enhancement of the photon strength function at low γ -ray energies was recently reported for several Mo isotopes. To study this enhancement further we have measured the spectra of two-step γ cascades following thermal neutron capture in 95 Mo. These spectra were compared with simulations of the γ decay of 96 Mo performed with the aid of the DICEBOX algorithm. Simulations with a large number of model combinations of photon strength functions for E1, M1, and E2 radiation are not consistent with the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…On the basis of a very few measured total radiation widths γ , it was suggested [7] that significant nonstatistical effects affected this decay. In contrast, it was found that the extreme statistical model was in very good agreement with two-step cascade γ spectra following thermal neutron capture [4] as well as coincidence-pulse-height spectra and other data for neutron-resonance capture [5].…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…On the basis of a very few measured total radiation widths γ , it was suggested [7] that significant nonstatistical effects affected this decay. In contrast, it was found that the extreme statistical model was in very good agreement with two-step cascade γ spectra following thermal neutron capture [4] as well as coincidence-pulse-height spectra and other data for neutron-resonance capture [5].…”
mentioning
confidence: 70%
“…Widely different shapes for the photon strength function (PSF), representing the decay strength as a function of γ -ray energy, have resulted from various measurements [1][2][3]. In addition, the enhancement in strength at low γ -ray energies reported for molybdenum isotopes [1,2] has been called into question [4,5], although more recent data [6] strongly support its existence. There is also disagreement about the nature of γ decay following neutron capture on molybdenum isotopes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the PSFs deduced from neutron-capture and 3 He-induced experiments indicate a γ-ray energy dependence which is different from the Lorentzian shape, but rather very similar to the model of Kadmenskii, Markushev and Furman. In some cases even these two types of reactions, (n, γ) and ( 3 He, 3 He ′ γ) or ( 3 He,αγ), are in disagreement [7]. As a result, the available experimental data is still challenging to explain fully the deexcitation γ-ray spectra from particle-induced reactions by the known photo-excitation modes in the nucleus.…”
mentioning
confidence: 88%